Esoteric images : decoding the late Herat school of painting - Daʻadli, Tawfiq, 1979- (Jerusalem Studies in Religion and Culture, 2019)
In Esoteric Images: Decoding the Late Herat School of Painting Tawfiq Daʿadli decodes the pictorial language which flourished in the city of Herat, modern Afghanistan, under the rule of the last Timurid ruler, Sultan Husayn Bayqara (r.1469-1506). This study focuses on one illustrated manuscript of a poem entitled Khamsa by the Persian poet Nizami Ganjavi, kept in the British Library under code Or.6810. Tawfiq Daʿadli decodes the paintings, reveals the syntax behind them and thus deciphers the message of the whole manuscript. The book combines scholarly efforts to interpret theological-political lessons embedded in one of the foremost Persian schools of art against the background of the court dynamic of an influential medieval power in its final years.